Does the adoption of Information and Communication Technologies improve the subjective well-being of citizens? A micro-level and city-level empirical investigation - Xiaodong Feng; Krishna Jayakar; Huiping Zhang; Zhiwei Tang (International Telecommunications Society (ITS), 2018)
This paper investigates the role of information and communication technologies (ICT) adoption and usage in enhancing the subjective well-being (SWB) of citizens, using the latest available China General Social Survey (CGSS) database. The impact is assessed using a two-level hierarchical linear model (HLM) accounting for both individual- and city-level characteristics. The findings suggest that government policies to increase the adoption of broadband and ICTs have implications beyond economic growth and opportunity, extending to the "happiness" of citizens.
Keywords: 330